PEMBELAJARAN SENI RUPA DUA DIMENSI DENGAN TEKNIK MOZAIK MENGUNAKAN BAHAN BUATAN PADA KELAS VIII D SMP NEGERI 2 PADANG PANJANG - Bayu Anggara; Andra Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the unique approach implemented at SMP Negeri 2 Padang Panjang in the use of mosaic techniques with synthetic materials for teaching two-dimensional art. This approach stands out because it differs from common practices at other schools, which tend to favor conventional drawing techniques or the use of natural materials. This study was conducted with the aim of describing in detail the learning process of two-dimensional art using the mosaic method based on artificial materials, as well as its impact on eighth-grade students in Class VIII D at the school. This study employs a descriptive qualitative approach using a case study design as its methodological framework. Data collection was carried out through several techniques, including direct field observations, in-depth interviews using a semi-structured questionnaire, documentation of learning activities, and a review of relevant literature. The research subjects consisted of 22 eighth-grade students in Class D, while supporting informants included the school principal, the art and culture teacher, and a number of students selected purposively. Learning activities were organized into three main phases: introductory activities, core activities, and concluding activities. The eighth-grade D students actively built their understanding through a series of practical activities, including creating initial sketches, cutting materials, and attaching heart-shaped foam pieces used as craft materials. The assessment results for the 12 groups’ projects showed an average score of 84.09, earning a B (Good) grade. More specifically, 4 groups achieved an A (Excellent) grade, 4 groups received a B (Good) grade, and the remaining 4 groups received a C (Fair) grade. Learning using this method has proven effective in comprehensively enhancing the creativity, fine motor skills, and aesthetic sensitivity of the eighth-grade D students